Production Management Strategy of the Music Group Interactive by CV. Maska Music Digital - Oktaviyandri, Adelfia (Universitas Negeri Surabaya, 2025)
Maska Music Digital is a management company founded by Septian Dwi Ratri (25 years old) in 2013. Then, in 2019, Maska Music Digital management formed a music group, Music Interactive, and developed it into a CV (Comannditaire Vennootschap). Maska Music Digital. The purpose of this study is to analyze the production management strategy of the Music Interactive group by CV. Maska Music Digital and analyze the obstacles and solutions to the management strategy. This research uses descriptive qualitative methods like observation, interview, and documentation techniques. Data analysis is done by reducing data, presenting data, and drawing conclusions, then discussing management theory and analyzing constraints and solutions using SWOT analysis—data findings related to implementing the Music Interactive group production management strategy by CV. Maska Music Digital includes planning, management, implementation, and Evaluation in music production, content production, and content publication of the Music Interactive group, as well as analyzing obstacles and solutions through SWOT analysis. CV. Maska Music Digital can produce music production, content production, and content publication for the Music Interactive group well and professionally.